2014
DOI: 10.1590/1982-0194201400011
|View full text |Cite
|
Sign up to set email alerts
|

Independent risk factors associated with infant deaths

Abstract: Objective: Identifying the independent risk factors associated with infant deaths registered in Brazilian public information systems. Methods: A cross-sectional study using secondary data recorded in public information systems for eleven years. The association of mortality rates was observed according to death periods using univariate and multivariate regression tests. Results: The infant mortality rate decreased by 20.7 % in the study period. The list of independent factors associated with infant deaths shows… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 8 publications
1
2
0
1
Order By: Relevance
“…20 There is evidence of a relationship between the access to health care services and socioeconomic conditions, in which municipalities with fewer areas of poverty, tend to have better access to services, however, within a reality of inequalities and social inequities, there are other limitations that compromise the reach of health care. 21 The interference of social risk factors as determinants of infant and fetal mortality, also explored in several Brazilian studies, 1,7,9,[11][12][22][23] is similar to the results found by the Floripa for Life Committee. These studies indicate that more than half of the deaths occurred in the neonatal period and were associated with mothers under 20 years of age; maternal schooling less than seven years; family income of between R$954 and R$1,908 or less; mothers who were cared for in public hospitals; difficulty in starting prenatal care; less than six medical consultations, among others related to the time of referral and attendance.…”
Section: Discussionsupporting
confidence: 60%
“…20 There is evidence of a relationship between the access to health care services and socioeconomic conditions, in which municipalities with fewer areas of poverty, tend to have better access to services, however, within a reality of inequalities and social inequities, there are other limitations that compromise the reach of health care. 21 The interference of social risk factors as determinants of infant and fetal mortality, also explored in several Brazilian studies, 1,7,9,[11][12][22][23] is similar to the results found by the Floripa for Life Committee. These studies indicate that more than half of the deaths occurred in the neonatal period and were associated with mothers under 20 years of age; maternal schooling less than seven years; family income of between R$954 and R$1,908 or less; mothers who were cared for in public hospitals; difficulty in starting prenatal care; less than six medical consultations, among others related to the time of referral and attendance.…”
Section: Discussionsupporting
confidence: 60%
“…[8][9][10] An increase in neonatal mortality risk is also associated with newborn characteristics, such as birth weight, gestational age and Apgar, among others. 5,[10][11] In the city of Cuiaba, capital of Mato Grosso (MT) state, neonatal mortality has been little studied, despite the high rates of neonatal deaths -8.7/1,000 live births in 2007 and 8.2/1,000 live births in 2010. [12][13] This study is therefore justified as it aimed to investigate the maternal and child risk factors, present in the Live Birth and Death Declaration, which were associated with neonatal mortality in Cuiabá-MT.…”
Section: Introductionmentioning
confidence: 99%
“…Observou-se diversidade também nas categorias de número de consultas realizadas durante a gestação:< e > 4 consultas; 0 a 3, 4 a 6 e 7 ou mais consultas; < e > 6 consultas e < e > 7 consultas (CARNEIRO et al, 2012;HASSAN et al, 2012;LIMA et al, 2012;GRANZOTTO;FONSECA;LINDEMANN, 2012;MAIA;MENDES, 2012;RIBEIRO et al, 2014;SINGH et al, 2014;SATO, 2014;DEBELEW;AFEWORK;YALEW, 2014;PEREIRA et al, 2014;SILVA;MATHIAS, 2014;YEGO et al, 2014;SILVA;ALMEIDA;ALENCAR, 2014;DHADED et al, 2015;KAMAL, 2015;LIMA et al, 2017).…”
Section: Resultsunclassified